Problems in Implementing Public Services in Indonesia and Legal Based Solution Strategies - Sri Yulianty Mozin; Filshabilla Wantu; Izzatunisa Akuba; Adelia Safitri Husain; Nirmawati Mahmud (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Public services are a state obligation to meet the basic needs of the community and have a strong legal basis through various laws and regulations in Indonesia. However, in practice, the implementation of public services still faces various problems such as slow service processes, unclear procedures, lack of transparency in costs and service times, and maladministration. This study aims to analyze the gap between the normative concept of public services and their implementation in practice and to identify factors that influence the low quality of public services. The research method used is a qualitative approach with library research through analysis of various literature, laws and regulations, and data from public service supervisory agencies. The results show that the main problems in public services in Indonesia are related to the weak implementation of service standards, low transparency and accountability, and suboptimal professionalism of the apparatus. In addition, maladministration practices such as prolonged delays and procedural deviations are still common. Digital transformation through the implementation of e-government is one effort to improve service quality, although its implementation still faces obstacles in human resources, infrastructure, and bureaucratic culture. Therefore, strengthening public service governance, increasing transparency, and optimizing oversight are necessary to ensure public services are more effective, accountable, and oriented toward the public interest.